2020
DOI: 10.3389/fvets.2020.00133
|View full text |Cite
|
Sign up to set email alerts
|

Life-Threatening Hemorrhage During Patent Ductus Arteriosus Ligation in a Cat: Xenotransfusion With Canine Blood

Abstract: A 13-month-old Sphynx cat was referred for patent ductus arteriosus (PDA) ligation. A left thoracotomy was performed and the PDA was efficiently ligated. Immediately after chest tube placement, it presented extensive intrathoracic bleeding from the caudal intercostal artery. In view of the absolute necessity of a blood transfusion and given that compatible feline blood was not available, xenotransfusion of canine blood was administered to the cat and resulted in a positive outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Consequently, there has been growing interest in the feasibility of canine to feline xenotransfusion for the treatment of severely anemic feline patients when compatible feline blood is not available. [4][5][6][7][8] No severe acute adverse reactions have been reported in cats receiving a single canine blood transfusion, and therefore xenotransfusion of canine blood to cats is now a recognized life-saving procedure when compatible feline blood is not available. [4][5][6][7][8] A delayed hemolytic transfusion reaction can be seen 1-6 days posttransfusion; however, the emergency transfusion can lead to temporary stabilization of the patient, allowing time for essential diagnostic procedures to be performed and a more suitable species-specific donor to be identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, there has been growing interest in the feasibility of canine to feline xenotransfusion for the treatment of severely anemic feline patients when compatible feline blood is not available. [4][5][6][7][8] No severe acute adverse reactions have been reported in cats receiving a single canine blood transfusion, and therefore xenotransfusion of canine blood to cats is now a recognized life-saving procedure when compatible feline blood is not available. [4][5][6][7][8] A delayed hemolytic transfusion reaction can be seen 1-6 days posttransfusion; however, the emergency transfusion can lead to temporary stabilization of the patient, allowing time for essential diagnostic procedures to be performed and a more suitable species-specific donor to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] No severe acute adverse reactions have been reported in cats receiving a single canine blood transfusion, and therefore xenotransfusion of canine blood to cats is now a recognized life-saving procedure when compatible feline blood is not available. [4][5][6][7][8] A delayed hemolytic transfusion reaction can be seen 1-6 days posttransfusion; however, the emergency transfusion can lead to temporary stabilization of the patient, allowing time for essential diagnostic procedures to be performed and a more suitable species-specific donor to be identified. [4][5][6][7][8] Crossmatches are in vitro tests to assess donor-recipient compatibility of blood products by assessing for agglutination and hemolysis prior to transfusion, which potentially decreases the risk of an adverse transfusion reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of availability of feline type B blood and the presence of natural alloantibody production in cats, there are several documented cases of cats being transfused with canine blood, with the first study of the practice being reported by Hessler et al (18), Euler et al (6), and Le Gal et al (16). More recently, a 13 month old Sphinx cat was transfused with 131 ml of canine blood due to hemorrhage from the caudal intercostal artery during patent ductus arteriosus ligation (19). Ultrasound-guided intracardiac xenotransfusion of canine 2 | Macroscopic Agglutination Score: 4+ incompatible reaction-one or two solid clumps with clear plasma; 3+ incompatible reaction-few to several large clumps with clear plasma; 2+ incompatible reaction-many medium-sized clumps with clear to cloud background; 1+ incompatible reaction-numerous small clumps; barely visible macroscopic aggregates with cloudy background; incompatible ±, erythrocyte aggregates observed on microscopic evaluation only; and compatible, no macroscopic or microscopic agglutination detected (displayed as "ns," as no agglutination was seen).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of availability of feline type B blood and the presence of natural alloantibody production in cats, there are several documented cases of cats being transfused with canine blood, with the first study of the practice being reported by Hessler et al ( 18 ), Euler et al ( 6 ), and Le Gal et al ( 16 ). More recently, a 13 month old Sphinx cat was transfused with 131 ml of canine blood due to hemorrhage from the caudal intercostal artery during patent ductus arteriosus ligation ( 19 ). Ultrasound-guided intracardiac xenotransfusion of canine packed red blood cells was used in emergency resuscitation of an 8-year-old cat with severe anemia from a massive flea infestation ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation